(untitled) (Лучшие интеллектуальные исследования, 2025)
Resume. The study of lung morphology under the influence of various diseases is of great interest to various areas of medicine and biology. In the experiment, the effect of morphological changes in the respiratory part of the lungs of rats was studied in the background of chronic kidney failure in 12-month-old white rats and compared with other diseases.